Nanosensors for regenerative medicine - Yeo, David C. (2014)
Assessing biodistribution, fate, and function of implanted therapeutic cells in preclinical animal experiments is critical to realize safe, effective and efficient treatments for subsequent implementation within the clinic. Currently, tissue histology, the most prevalent analytical technique to meet this need, is limited by end-point analysis, high cost and long preparation time. Moreover, it is disadvantaged by an inability to monitor in real-time, qualitative interpretation and ethical issues arising from animal sacrifice. While genetic engineering techniques allow cells to express molecules with detectable signals (e.g., fluorescence, luminescence, T1 (spin–lattice)/T2 (spin–spin) contrast in magnetic resonance imaging, radionuclide), concerns arise regarding technical complexity, high-cost of genetic manipulation, as well as mutagenic cell dysfunction. Alternatively, cells can be labeled using nanoparticle-sensors—nanosensors that emit signals to identify cell location, status and function in a simple, cost-effective, and non-genetic manner. This review article provides the definition, classification, evolution, and applications of nanosensor technology and focuses on how they can be utilized in regenerative medicine. Several examples of direct applications include: (1) monitoring post-transplantation cell behavior, (2) revealing host response following foreign biomaterial implantation, and (3) optimization of cell bioprocess operating conditions. Incorporating nanosensors is expected to expedite the development of cell-based regenerative medicine therapeutics.